The determination of heavy metals in coal ash - Michelle Christine, Miod (Universiti Malaysia Sarawak, UNIMAS, 2008)
Sejingkat Power Corporation Sdn. Bhd., is a coal-fired power which is located near Bako generates energy and electricity. Combustion of coals in coal-fired power plant generates huge amounts of ashes. When coal is burnt, it produces coal ash into the environment. Ash samples were collected from the ash pond in five different depths at eight different locations. The analyses of heavy metals were done in each depth of the different locations. The concentrations of heavy metals such as Cd, Mn, Zn, Pb and Ni in coal ash were analyzed using Atomic Absorption Spectrometry (AAS) method. Pb was found to have the highest concentration in the ash samples, followed by Zn and Ni. The mean concentrations of heavy metals were found to be in a following order in the ash samples: Mn < Cd < Ni < Zn < Pb. Among the five heavy metals, Pb is most abundant in the coal ash pond compared to Zn, Ni, Cd and Mn.